2021
DOI: 10.1249/mss.0000000000002832
|View full text |Cite
|
Sign up to set email alerts
|

Highly Cushioned Shoes Improve Running Performance in Both the Absence and Presence of Muscle Damage

Abstract: PurposeWe tested the hypotheses that a highly cushioned running shoe (HCS) would 1) improve incremental exercise performance and reduce the oxygen cost (Oc) of submaximal running, and 2) attenuate the deterioration in Oc elicited by muscle damage consequent to a downhill run.MethodsThirty-two recreationally active participants completed an incremental treadmill test in an HCS and a control running shoe (CON) for the determination of Oc and maximal performance. Subsequently, participants were pair matched and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Other studies have analyzed the effect of footwear on the resulting fatigue. Black et al [40] determined the influence of using a highly cushioned model on the muscle damage resulted after 30 minutes of downhill run at a moderate intensity compared to a control model with less compliant and resilient midsole properties. Although there was no significant main effect of footwear on the extent of muscle damage observed, the firstly improved RE (~ 3.2 %) with the highly cushioned model was further reduced 48 hours after (~ 4.6 %) [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have analyzed the effect of footwear on the resulting fatigue. Black et al [40] determined the influence of using a highly cushioned model on the muscle damage resulted after 30 minutes of downhill run at a moderate intensity compared to a control model with less compliant and resilient midsole properties. Although there was no significant main effect of footwear on the extent of muscle damage observed, the firstly improved RE (~ 3.2 %) with the highly cushioned model was further reduced 48 hours after (~ 4.6 %) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Black et al [40] determined the influence of using a highly cushioned model on the muscle damage resulted after 30 minutes of downhill run at a moderate intensity compared to a control model with less compliant and resilient midsole properties. Although there was no significant main effect of footwear on the extent of muscle damage observed, the firstly improved RE (~ 3.2 %) with the highly cushioned model was further reduced 48 hours after (~ 4.6 %) [40]. Likewise, Vercruyssen et al [13] observed a greater RE deterioration when using the Salomon Sense minimal model compared to the Salomon XT traditional model after completing a trail running course.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that highly cushioned shoes (i.e. those with similar material characteristics to the VPF shoe model) improve incremental exercise performance and RE in absence and presence of muscle damage (Black et al, 2022). This aspect can be relevant for training adaptations for runners who could tolerate more training volume at the same intensity or the same volume at higher intensity if they use this type of footwear more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…This type of shoe is more commonly used in competition, although it also can be used in high‐intensity training sessions such as short‐ and long‐interval training. Black et al (2022) have reported improvements in incremental exercise performance and RE with the absence and presence of muscle damage in a highly cushioned shoes with a midsole more compliant and resilient (as the VPF model) when compared to traditional shoes. These findings are relevant as runners using this type of shoe that can improve RE and the physiological and perceived effort, which ultimately may allow to train a greater volume than using other models (Black et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation